Travels through the Orient and the Mediterranean world : essays presented to Eric Gubel. (Orientalia Lovaniensia analecta., 2021)
This volume brings together 36 contributions dedicated to Eric Gubel on the occasion of his retirement as head of the Department of Antiquity at the Royal Museums of Art and History, Brussels. Colleagues bring homage to a scholar who made an invaluable mark in the field of Phoenician studies and who spearheaded research, publication and exhibition projects on the archaeology, history, and art of Western Asia and the Mediterranean world. Eric Gubel's research on Egyptian, Levantine, Cypriot, Syrian, and Mesopotamian artistic expressions and interconnections permeated his academic teaching career and is found in the extensive list of publications that opens the volume. To pay tribute to the honoree's wide-ranging field of interest, this collection of essays is conceived as a voyage from Mesopotamia and the Gulf Region through Syria and the Levant to the Phoenician and Punic West. The volume focuses on Antiquity and its reception in contemporary society. The papers, dealing with architecture and urbanism, ceramics, figurines, ivories, metal bowls, seal-amulets, coins, languages and inscriptions, chronology, iconography, identity, and comics, will appeal to anyone interested in the ancient world.